Leitura e produção de histórias em quadrinhos: uma proposta de multiletramentos pautada na Gramática do Design Visual e em aulas do Portal do Professor - Guisardi, Conceição Maria Alves de Araújo (2015)
This dissertation is the result of a research applied in two Brazilian public schools, at two classes of the 9th grade, elementary school. The proposal aims to contribute to multiliteracies practices in school, through reading activities and production of comic books. The need for the research came from the student\'s exposure scenario to technologies, contributing to the constant access to multimodal genres. Rojo (2014) says that the multiple requirements of the technological world will multiply greatly the practices and texts that circulate and are addressed. Studies of discourse genres (BAKHTIN, 2003[1979]), Multiliteracies (ROJO,2012;2013) and Multimodality (KRESS; VAN LEEUWEN, (2006 [1996]) represent the main theoretical basis on which our proposal is centered. We elaborated a proposal for reading and production of comic books in paper and digital. For it, we used suggestions classes of the Teacher´s Portal (Portal do Professor/MEC). We explored some meanings of the grammar of Visual Design, theory of the Reading Images: the grammar of visual design, authored by Kress and van Leeuwen (2006 [1996]) that follows the functionalist thinking of Systemic functional Linguistics of the Halliday (1985[1978]). The students developed the reading practice and production practice of Digital Comics and printed; we used the available technological resources, exploring the theme \"social inclusion\" and other themes that emerged from this. And, for the production of Digital Comics, we used the program Pixton for schools, because we have the license and we offered for our students. All productions of the students have been published in the program, available to be getting and shared and can be as support material for students and teachers of the two schools as well as from other institutions. We created, two Photobooks (one for each school) with the productions of the students, too, and that final product became part of the collection of the libraries of the two schools, staying available for other classes and teachers may have access. We point out that the lack of technological resources still represents a barrier that discourages students and causes them to be inserted into a digital divide that affects a lot of public institutions in the country. Despite the obstacles, we believe that students enjoy reading and producing comics, both in printed version as digital and that work with Comics and other multimodal genres can contribute, for training of students, in addition to improving its practices of reading and writing.